2016
DOI: 10.1103/physrevb.94.035111
|View full text |Cite
|
Sign up to set email alerts
|

Nonmonotonic anisotropy in charge conduction induced by antiferrodistortive transition in metallicSrTiO3

Abstract: Cubic SrTiO3 becomes tetragonal below 105 K. The antiferrodistortive (AFD) distortion leads to clockwise and counter-clockwise rotation of adjacent TiO6 octahedra. This insulator becomes a metal upon the introduction of extremely low concentration of n-type dopants. However, signatures of the structural phase transition in charge conduction have remained elusive. Employing the Montgomery technique, we succeed in resolving the anisotropy of charge conductivity induced by the AFD transition, in the presence of d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 59 publications
3
24
0
Order By: Relevance
“…Above 50K, it starts a significant shift upward and exceeds 3 around 150K, before steadily decreasing afterwards. The antiferrodistortive transition [40] is the source of the small anomaly at 105K. resistivity prefactor and their electronic specific heat.…”
Section: Resultsmentioning
confidence: 99%
“…Above 50K, it starts a significant shift upward and exceeds 3 around 150K, before steadily decreasing afterwards. The antiferrodistortive transition [40] is the source of the small anomaly at 105K. resistivity prefactor and their electronic specific heat.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally driven anisotropy in the Fermi surface could potentially alter T c . First-principles calculations of the Fermi surface in bulk electron-doped STO showed that the tetragonal anisotropy produces a considerable distortion in the Fermi surface, compressing it along the c direction by as much as 35% [51]. In our δ-doped material, the Fermi surface is dramatically altered from the bulk by confinement in the vertical direction [29], yet despite the change in dimensionality, the overall scale of Tc in our N D = 1 at.% Nb δ-doped material is within the range of peak T c s observed for material doped in the bulk [1,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The AFD transition is extremely sensitive to the presence of a tiny amount of extrinsic atoms. Introducing oxygen vacancies reduces T AF D [56,57]. However, substituting Ti with Nb shifts it upward.…”
Section: The Crystal Lattice Of Srtio3mentioning
confidence: 99%
“…However, substituting Ti with Nb shifts it upward. Substitution of Sr with La or Ca is beneficial for T AF D [57,58], but it is detrimental with Ba and Pb [59]. McCalla et al [60] have recently examined in detail the complex response of T AF D to substitution and proposed a unified picture to explain it that is based on a combination of impurityinduced change in the Goldschmidt tolerance factor and the ionic valence mismatch between the host and the impurity.…”
Section: The Crystal Lattice Of Srtio3mentioning
confidence: 99%